Penegakan Hukum Perdata dalam Penyelesaian Peredaran Rokok Ilegal - Indrajaya Indrajaya (Universitas Batanghari Jambi, 2025)
The circulation of illegal cigarettes is a serious problem, impacting not only health but also state revenue from the tax sector and creating unfair business competition. In practice, the resolution of illegal cigarette circulation is not only carried out through a criminal approach but also uses administrative and civil law instruments related to dispute resolution for parties harmed by the circulation of illegal cigarettes. The problem in this paper is how the civil settlement mechanism for illegal cigarette dealers in practice. The type of research method used in writing this journal is normative juridical research using the statute approach and the case approach. From the results of the discussion, it can be concluded that the civil settlement mechanism for illegal cigarette dealers is to pay compensation to the state, either through the courts or customs officers, a maximum of 7 times the price of the illegal cigarettes.